(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The use of information and communication technology i.e. ICT in education is a comparatively new experience.ICT is defined as a set of human interactive tools, electronic devices and resources used for communication. ICT services and features variously support teaching, learning and a sort of activities in education.ICT makes the use of information technology and communication technology. In this paper we are discussing education methodology incorporate with ICT.E-learning through ICT is an upcoming era of teaching learning process.